Clinical Clostridium difficile: clonality and pathogenicity locus diversity. - Kate E Dingle (Public Library of Science (PLoS), 2011)
Clostridium difficile infection (CDI) is an important cause of mortality and morbidity in healthcare settings. The major virulence determinants are large clostridial toxins, toxin A (tcdA) and toxin B (tcdB), encoded within the pathogenicity locus (PaLoc). Isolates vary in pathogenicity from hypervirulent PCR-ribotypes 027 and 078 with high mortality, to benign non-toxigenic strains carried asymptomatically. The relative pathogenicity of most toxigenic genotypes is still unclear, but may be influenced by PaLoc genetic variant. This is the largest study of C. difficile molecular epidemiology performed to date, in which a representative collection of recent isolates (n = 1290) from patients with CDI in Oxfordshire, UK, was genotyped by multilocus sequence typing. The population structure was described using NeighborNet and ClonalFrame. Sequence variation within toxin B (tcdB) and its negative regulator (tcdC), was mapped onto the population structure. The 69 Sequence Types (ST) showed evidence for homologous recombination with an effect on genetic diversification four times lower than mutation. Five previously recognised genetic groups or clades persisted, designated 1 to 5, each having a strikingly congruent association with tcdB and tcdC variants. Hypervirulent ST-11 (078) was the only member of clade 5, which was divergent from the other four clades within the MLST loci. However, it was closely related to the other clades within the tcdB and tcdC loci. ST-11 (078) may represent a divergent formerly non-toxigenic strain that acquired the PaLoc (at least) by genetic recombination. This study focused on human clinical isolates collected from a single geographic location, to achieve a uniquely high density of sampling. It sets a baseline of MLST data for future comparative studies investigating genotype virulence potential (using clinical severity data for these isolates), possible reservoirs of human CDI, and the evolutionary origins of hypervirulent strains.